THU0481 THE PREVALENCE OF CHRONIC MUSCULOSKELETAL PAIN IN PATIENTS WITH ULCERATIVE COLITIS IN COMPARISON TO CONTROLS FROM THE GENERAL POPULATION: A CROSS-SECTIONAL STUDY. (2nd June 2020) - Pettersson, N.; Kragsbjerg, F.; Hamrin, A.; Bergman, S.; Forsblad-D'elia, H.; Karling, P.
Abstract : Background: Musculoskeletal symptoms are common in patients with ulcerative colitis (UC) but the knowledge of the prevalence of chronic regional pain (ChRP) and chronic widespread pain (ChWP) in patients with UC is scarce. Objectives: To compare the prevalence of ChRP, ChWP and chronic pain in different body locations in patients with UC with controls from the general population and to investigate if disease activity in UC is related to chronic pain. Methods: From a national inflammatory bowel disease (IBD) Register (SWIBREG), all living patients with a confirmed UC diagnosis, aged 20-74 years (n=1134), who were residents in two counties in Northern Sweden were posted a validated questionnaire. Persons from the general population from a previous study (1) using the same questionnaires was used as controls (n=3867). The questionnaire comprises demography, history of pain and body localisation of pain. The disease activity of UC was measured by Patient- Simple Clinical Colitis Activity Index (P-SCCAI). ChRP and ChWP was defined as having pain for at least three months the last year. ChWP was defined as having pain on both left and right side of the body and both above and below the waist, and in the axial part of the body. Results: The response rate for the patients with UC was 49.0% and for the controls 62.7%. The patients were older than the controls (mean age 52.8 vs 46.5 years; p<0.001) but there was no difference in gender (men 50.5% vs 46.7%; p=0.086). The reported prevalence of any chronic pain, ChRP and ChWP was higher in patients with UC versus controls (54.4% vs 39.5%; p<0.001; 32.5% vs 24.2%; p<0.001 and 19.4% vs 12.5%; p<0.001). The differences for reported chronic pain (any pain) was seen in all age groups. The patients with UC reported significantly more pain in the regions "lower back", "hip/upper leg" and "lower leg/foot" compared to controls (Table ). The patients with P-SSCAI >5 (n=121) reported more ChWP than patients with P-SSCAI <5 (n=426) (46.3% vs 12.7%; p<0.001) and controls (46.3% vs 12.5%; p<0.001) with significant differences compared to controls in all body regions. No significant difference in ChWP was found between patients with P-SSCAI <5 and controls (12.7% vs 12.5%; p=0.917). There was a slightly higher prevalence of reported any chronic pain between patients with P-SSCAI <5 and controls (46.5% vs 39.5%; p=0.007). Conclusion: Patients with UC reported more chronic pain than controls from the general population, especially from the lower back and hip region. Higher UC disease activity was associated with more pain in all body regions. References: [1]Bergman S, Herrstrom P, Hogstrom K, Petersson IF, Svensson B, Jacobsson LT. Chronic musculoskeletal pain, prevalence rates, and sociodemographic associations in a swedish population study. J Rheumatol 2001;28:1369-77. Disclosure of Interests: Nina Pettersson: None declared, Fredrik Kragsbjerg: None declared, Arvid Hamrin: None declared, Stefan Bergman: None declared, Helena Forsblad-d'Elia Grant/research support from: Unrestricted grant from Novartis., Consultant of: Advisory Board Fees from Sandoz, Novartis, and Abbvie, Pontus Karling: None declared